El Commercio Electrónio y el papel de la OMC - Marc Bacchetta; Patrick Low; Aaditya Mattoo; Ludger Schuknecht; Hannu Wager; Madelon Wehrens (World Trade Organization (WTO), 1998)
Un estudio efectuado por la Secretaría de la OMC, El comercio electrónico y el papel de la OMC, analiza los beneficios que la utilización de Internet para fines comerciales puede suponer para el comercio en general. El informe, obra de un equipo de economistas de la Secretaría de la OMC, expone a grandes rasgos los elementos complejos y los posibles beneficios del comercio por conducto de Internet. – – The study was written as a means of providing background information for the 132 WTO members who are now developing policy responses to this new form of commerce. Written by a team of economists from the WTO Secretariat, it identifies the complexities as well as the potential benefits of trade via the Internet. The book describes the extraordinary expansion of opportunities that electronic commerce offers, including for developing countries.
Keywords: 330